Groundwater Quality: Focus on Fluoride in Selected Villages of S.P.S.R. Nellore District, Andhra Pradesh, India - Rao Kameswara O.; Venkateswarlu P. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
The fluoride concentration in underground water was determined in five revenue mandals of s.p.s.r.nellore district. Six villages from each block were identified to measure fluoride concentration along with other water quality parameters. The fluoride concentration in the underground water varied from 1.05 to 8.43mg/l, which is alarming and foresee to be causing skeletal fluorosis among people especially children of these villages. To stop further disgrace it is immediately required to treat the fluoride contaminated waters of these villages with suitable and cost effective defluoridation techniques.